DEVELOPMENT OF DIGITAL COMPETENCIES OF PRIMARY SCHOOL TEACHERS THROUGH BUILDING KNOWLEDGE AND SKILLS FOR WORKING WITH VISUAL PROGRAMMING ENVIRONMENT WITHIN MATH PROJECT WORK - Papancheva, Rumyana Y; Karadimitrova, Rumyana (Journal of process management and new technologies, 2017)
The paper presents a review of the contemporary school, the digital generation and the need of teachers equipped with new knowledge and skills, in particular – basic programming skills. The last change of educational system in Bulgaria after the adoption of the new pre-school and general school education act is analysed. New primary school curricula and new standards for teacher’s qualification were implemented. The new school subject “Computer modelling” is presented. Some experience of the authors from project-based work in mathematics with teachers and students is described. The aim is the formation of skills of programing by working within Scratch – visual environment for block-based coding. Some conclusions and ideas for future work are formulated.